Antecedent of Organizational Innovation in the Sulawesi Electric Power Industry - Emerald Brilliant Kussoy; Andreas Wahyu Gunawan P (Budapest International Research and Critics University, 2022)
This study examine the relationship between of organizational culture and organizational innovation in supporting increased work engagement, organizational citizenship behavior, and knowledge sharing. This study results describe the involvement of work culture on how important knowledge sharing has an impact on organizational innovation. This study develops the influence of organizational culture on perceptions of work engagement, organizational citizenship behavior, good knowledge sharing and encourages a higher level of willingness to innovate and will ultimately affect organizational innovation. The four variables were developed into 35 measurement indicators. There are 4 (four) hypotheses tested to analyze Antecedent of Organizational Innovation in the Electric Power Industry in Sulawesi industry. The research findings show that from the development of 4 (four) hypotheses, there are 4 (four) hypotheses which have been proven to have a significant and positive.